STUDY OF TINEA PEDIS IN DIABETIC VERSUS NON-DIABETIC PATIENTS - Al-Ani, Yasir Mansour Mohamed (AL-Kindy College Medical Journal, 2020)
Background : The aim of this work is to study the clinical features and causative fungi of tinea pedis in diabetic and non-diabetic patients. Result : Tinea pedis was estimated to be the second most common skin disease in the United States, after acne. Up to 15% of the U.S., population may have tinea pedis. Across Europe and East Asia, prevalence rates reach 20 %. Methods: The Complete history taking regarding: age, sex, occupation, residency, history of diabetes and diabetic profile (fasting blood sugar and post prandial).and Clinical examination of the feet Aim of the study : The aim of this work was to study the clinical features and causative fungi of tinea pedis in diabetic and non-diabetic patients Conclusion : Tinea pedis is more frequent in tropical climates and may be associated with use of occlusive footwear. Males are more often affected than females. It is mostly affecting the web space between the fourth and fifth toes. Children do not often develop tinea pedis. Patients with atopic dermatitis or immuno suppressive disorders may be predisposed to developing tinea pedis